Julio BORREGO NIETO (dir.), Lorena DOMÍNGUEZ GARCÍA, Sheila LUCAS LASTRA, Álvaro RECIO DIEGO & Carmela TOMÉ CORNEJO: Gramática de referencia para la enseñanza del español. La combinación de oraciones, 2013, 432 pp. - Suárez Rodríguez, Beatriz Pilar (Moenia, 2016)